Klasifikasi Artikel Berita Online Sederhana dengan Menggunakan Struktur Kategori Wikipedia - William Aprilius (Faculty of Engineering and Informatics, Universitas Multimedia Nusantara, 2014)
The growth of information and communication technology makes the electronic news portal as a source of information. It makes the increasing numbers of online news articles that need to be classified. The classification is done to facilitate the users to access news. This paper proposes a simple method of classification of online news articles into categories. This method uses Wikipedia Bahasa Indonesia as a source of external knowledge and consists of 6 steps. In general, this method works by exploiting the structure of categories in Wikipedia, then check for the existence of entities of a news article in Wikipedia articles. This paper is an early stage of the research to be conducted and the proposed method has not been implemented. This makes the researchers have not been able to draw conclusions with regard to the method proposed. Index Terms—news classification, text classification, Wikipedia